Penerapan Pembelajaran Berdiferensiasi Dengan Memanfaatkan Kecerdasan Majemuk (Visual-Spasial dan Kinestetik) Pada Materi Pengukuran Panjang Siswa Kelas II UPT SD Negeri Babadan 03 - Qomariyah, Nurul; Surayanah (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2026)
This research aims to examine the implementation of differentiated learning leveraging multiple intelligences, specifically focusing on visual-spatial and kinesthetic intelligences, for the topic of length measurement in Grade II at UPT SD Negeri Babadan 03. Employing a descriptive qualitative approach, data were collected through interviews, observation, and documentation. The study is grounded in the diversity of students' learning styles and characteristics, seeking to identify adaptive and inclusive instructional strategies. Conducted over three sessions, the learning process implemented differentiation in content, process, and product. Strategies were varied to meet specific needs: visual-spatial students utilized instructional videos, while kinesthetic students engaged in ice-breaking activities, teacher demonstrations, and hands-on measurement of objects within the school environment. The implementation resulted in a positive impact on learning comprehension. Qualitatively, visual media effectively directed student focus, while practical activities increased enthusiasm and active engagement in mastering concrete measurement concepts. Despite minor challenges regarding classroom atmosphere during group work and practical sessions, these issues were successfully mitigated through effective classroom management and clear guidance. Ultimately, the research concludes that combining differentiated learning with multiple intelligences is highly effective in enhancing the understanding of mathematical concepts and fostering a joyful, meaningful learning environment for elementary school students